Chorological study of the genus "Filago" L. ("Asteraceae, Gnaphalieae") in the Iberian Peninsula and Balearic Islands - Andrés-Sánchez, Santiago; Martínez-Ortega, María Montserrat; Rico, Enrique (Botanica Complutensis, 2013)
The taxonomical complexity of the genus Filago has traditionally led to many determination mistakes which have hampered a precise knowledge of the exact distribution areas of the species included in the genus. We have tried to compile all the available data on the distribution in the Iberian Peninsula and Balearic Islands of 20 taxa from the genus Filago and have critically revised them. As a result, in 13 cases we report the presence of a particular species of Filago for the first time at the provincial level. The distribution ranges of F. gaditana, F. germanica, F. lutescens subsp. atlantica and F. micropodioides traditionally hindered by taxonomic and nomenclatural problems are reliably circumscribed. Last and remarkably, according to our results, F. asterisciflora is not present in the Iberian Peninsula and in the Balearic Islands.
Keywords: chorology; Spain; Portugal; Balearic Islands; Filago; Evax; Logfia; new records